The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
The Encyclopedia of Peace Psychology 2011
DOI: 10.1002/9780470672532.wbepp032
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Violence

Abstract: Rapid global climate change is now a fact of twenty‐first century life. Human activity especially the production of huge quantities of several greenhouse gases primarily from the burning of fossil fuels, has initiated a general warming trend in our atmosphere and on our planet. This trend will continue and likely will accelerate unless we find a way to return the composition of our atmosphere to a pre‐industrial era norm. Because of the longevity of greenhouse gases, even a slowing of the warming trend won't o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 5 publications
2
17
0
2
Order By: Relevance
“…There are several mechanisms for this (Agnew, ). One is the well‐known impact of heat on aggression (Anderson, , ). Another is increased competition for diminishing environmental resources, such as clean water and arable land.…”
Section: Intergroup Relationsmentioning
confidence: 99%
“…There are several mechanisms for this (Agnew, ). One is the well‐known impact of heat on aggression (Anderson, , ). Another is increased competition for diminishing environmental resources, such as clean water and arable land.…”
Section: Intergroup Relationsmentioning
confidence: 99%
“…Drought-related worry and psychological distress There may be a link between extreme heat (climate change related or otherwise) and increasing violence, aggressive motives, and/or aggressive behavior. 80,92,93,94 The frequency of interpersonal violence and intergroup conflict may increase with more extreme precipitation and hotter temperatures. 83 These impacts can include heightened aggression, which may result in increased interpersonal violence and violent crime, negatively impacting individual and societal mental health and well-being.…”
Section: Droughtmentioning
confidence: 99%
“…The impact of extreme heat on mental health is associated with increased incidence of disease and death, aggressive behavior, violence, and suicide and increases in hospital and emergency room admissions for those with mental health or psychiatric conditions. 80,81,82,83,84,85,86,87 Individuals with mental illness are especially vulnerable to extreme heat or heat waves. In six case-control studies involving 1,065 heat wave-related deaths, preexisting mental illness was found to triple the risk of death due to heat wave exposure.…”
Section: Droughtmentioning
confidence: 99%
“…Voluminous of literatures have relate the incidences of changing weather or climate change to criminal activities. Climate change can even lead to social conflict that includes interstate conflict, civil war and conflict between smaller groups within states (Agnew, 2011;Anderson, 2012). Agnew (2011) posits that strains such as anger, frustration and fear can be impacted by climate change.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce or escape from strain people will resort to crime. Anderson (2012) argues that global warming can result an uncomfortably warm temperature that could instigate irritability, aggression and violent behaviour, and thus, risking children to be violence-prone individuals as well as exposing the livelihood and survival of the population to sudden risk. For example, extreme weather such as floods, hurricanes, droughts, wildfires and blackouts which have devastating effects that can lead to physical injury, death, displacement of people, destruction of homes, properties and infrastructures, loss of livelihood, shortages of fresh water and food, occurrences of diseases, disruption of routine activitiesall these lead to additional strains.…”
Section: Introductionmentioning
confidence: 99%